2019
DOI: 10.1002/eat.23200
|View full text |Cite
|
Sign up to set email alerts
|

Parents know best: Caregiver perspectives on eating disorder recovery

Abstract: Objective: This study used mixed methods to evaluate caregiver perspectives on recovery from an eating disorder.Method: Caregivers (N = 387) completed an online survey about their child's weight history, treatment history, illness trajectory, and recovery. Results:Children were predominantly females with adolescent onset anorexia nervosa and currently 18.4 years old on average. Qualitative analysis of caregivers' open-ended definitions of recovery revealed seven distinct recovery domains, including 1) weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Parents of youths with an eating disorder have highlighted the lengthiness of the recovery process [ 35 ]. In a survey of parents of youths who had a diagnosis of an eating disorder, only 20% reported that their child had completely recovered, and reported that physical recovery preceded cognitive recovery [ 1 ]. Treatment with a focus on improving quality of life has been recommended as a follow-up support, after reduction of eating disorder symptoms has been achieved [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents of youths with an eating disorder have highlighted the lengthiness of the recovery process [ 35 ]. In a survey of parents of youths who had a diagnosis of an eating disorder, only 20% reported that their child had completely recovered, and reported that physical recovery preceded cognitive recovery [ 1 ]. Treatment with a focus on improving quality of life has been recommended as a follow-up support, after reduction of eating disorder symptoms has been achieved [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver perspectives on ED recovery have been neglected despite their clinical significance (Accurso, Sim, Muhlheim, & Lebow, 2020). The ED‐15‐P is the first caregiver report measure of ED psychopathology that enables tracking of session‐to‐session change.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of parents of youth who had a diagnosis of an eating disorder, only 20% reported that their child had completely recovered, and reported that physical recovery preceded cognitive recovery (Accurso, Sim, Muhlheim & Lebow, 2020). Treatment with a focus on improving quality of life has been recommended as a follow-up support, after reduction of eating disorder symptoms has been achieved (Accurso et al, 2020). However, the literature suggests a portion of youth and families who would bene t from further eating disorder follow-up care are not offered this option.…”
Section: Discussionmentioning
confidence: 99%